2020
DOI: 10.1103/physrevc.102.035201
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy doubly virtual Compton scattering from dilepton electroproduction on a nucleon

Abstract: We propose a new way to experimentally determine the subleading low-energy structure constant of doubly virtual Compton scattering on a proton. Such empirical determination will reduce the theoretical model error in estimates of the hadronic correction to the muonic hydrogen Lamb shift. We demonstrate that the dilepton forward-backward asymmetry in the e − p → e − p e − e + process, which can be accessed at electron scattering facilities, yields a large sensitivity to this so far unknown low-energy constant.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…For the near-forward real Compton cross section (i.e. integrated over dilepton phase space), it was found that around W = 1.25 GeV the Born + ∆(1232)-pole contribution reproduces a full dispersive calculation based on empirical structure functions within an accuracy of 5% or better [21]. As we consider in this work kinematics around the ∆(1232) resonance, we will study as a first step the effect due to radiative corrections on the ∆(1232)-pole contribution.…”
Section: ∆-Pole Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…For the near-forward real Compton cross section (i.e. integrated over dilepton phase space), it was found that around W = 1.25 GeV the Born + ∆(1232)-pole contribution reproduces a full dispersive calculation based on empirical structure functions within an accuracy of 5% or better [21]. As we consider in this work kinematics around the ∆(1232) resonance, we will study as a first step the effect due to radiative corrections on the ∆(1232)-pole contribution.…”
Section: ∆-Pole Modelmentioning
confidence: 99%
“…The resulting uncertainty due to this subtraction term constitutes at present the main uncertainty in the theoretical µH Lamb shift estimate. To reduce such model dependence, the dilepton electroproduction process on a proton has been proposed in [21] as an empirical way to determine T 1 (0).…”
Section: Low-energy Expansionmentioning
confidence: 99%
See 1 more Smart Citation
“…For these methods, the TPE correction is usually divided into Born and non-Born pieces, where the Born part is well-constrained by the experimental data, but the non-Born part contains a subtraction function, which is poorly constrained and relies on model, thus leading to a large systematic uncertainty. It is proposed recently that the subtraction function can be further constrained by the dilepton electroproduction [22]. To date, the theoretical results of the TPE correction ∆E TPE are summarized in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Other theoretical approaches are usually devoted to improve the determination of the non-Born contribution, in particular the contribution of subtraction function. It has also been recently proposed that the subtraction function can be further constrained by the dilepton electroproduction [18].…”
Section: Introductionmentioning
confidence: 99%